Defining the Medical Library Association research agenda: methodology and final results from a consensus process. - Eldredge JD; Harris MR; Ascher MT (Journal of the Medical Library Association, 2009)
OBJECTIVE: Using a group consensus methodology, the research sought to generate a list of the twelve to fifteen most important and answerable research questions in health sciences librarianship as part of a broader effort to implement the new Medical Library Association (MLA) research policy. METHODS: The delphi method was used. The committee distributed a brief survey to all estimated 827 MLA leaders and 237 MLA Research Section members, requesting they submit what they considered to be the most important and answerable research questions facing the profession. The submitted questions were then subjected to 2 rounds of voting to produce a short list of top-ranked questions. RESULTS: The survey produced 62 questions from 54 MLA leaders and MLA Research Section members, who responded from an estimated potential population of 1,064 targeted colleagues. These questions were considered by the process participants to be the most important and answerable research questions facing the profession. Through 2 rounds of voting, these 62 questions were reduced to the final 12 highest priority questions. CONCLUSION: The modified delphi method accomplished its desired survey and consensus goals. Future survey and consensus processes will be revised to generate more initial questions and to distill a larger number of ranked prioritized research questions.